Sensory system integration of the designed mechatronics Touch Hand. Issue 2 (21st March 2016) - van der Riet, Drew; Stopforth, Riaan; Bright, Glen; Diegel, Olaf
Abstract : Purpose: This paper aims to explore the electronic design of the Touch Hand: a low-cost electrically powered prosthetic hand. The hand is equipped with an array of sensors allowing for position control and haptic sensation. Pressure sensors are used on the fingertips to detect grip force. A temperature sensor placed in the fingertip is used to measure the contact temperature of objects. Investigations are made into the use of cantilever vibration sensors to detect surface texture and object slippage. The hand is capable of performing a lateral grip of 3.7 N, a power grip of 19.5 N and to passively hold a weight of up to 8 kg with a hook grip. The hand is also tested on an amputee and used to perform basic tasks. The amputee took 30 min to learn how to operate the hands basic gripping functions. Design/methodology/approach: Problems of previous prosthetic hands were investigated, followed by ways to improve or have similar capabilities, yet keeping in mind to reduce the price. The hand was then designed, simulated, developed and then tested. The hand was then displayed to public and tested with an amputee. Findings: The Touch Hand's capabilities with the usage of the low-cost materials, components and sensory system was obtained in the tests that were conducted. The results are shown in this paper to identify the appropriateness of the sensors for a usage while the costs are reduced. Furthermore, models were developed from the results obtained to take into account factors such as the non-slip material. Research limitations/implications: The research was restricted to a US1, 000 budget to allow the availability of a low-cost prosthetic hand. Practical implications: The Touch Hand had to have the ability to supply the amputee with haptic feedback while allowing the basic grasping of objects. The commercial value is the availability of an affordable prosthetic hand that can be used by amputees in Africa and other Lower-Income countries, yet allowing a more advanced control system compared to the pure mechanical systems currently available. Social implications: The Touch Hand has the ability to give amputees affected in war situations the ability to grasp objects in a more affordable manner compared to the current available options. Feedback from amputees about the current features of the Touch Hand was very positive and it proves to be a way to improve society in Lower-Income countries in the near future. A sponsorship program is being developed to assist amputees with the costs of the Touch Hand. Originality/value: The contributions of this research is a low-cost prototype system than can be commercialized to allow amputees in the Lower-Income countries to have the ability of a prosthetic hand. A sensory system in the hand is also explained which other low-cost prosthetic hands do not have, which includes temperature, force and vibration. Models of the sensors used that are developed and calibrated to the design of the hand are also described.